The archaeological mission of the National Academy of Sciences of the Republic of Armenia and the National Research Council of Italy, 1994-2014 - Biscione, Raffaele; Hmayakyan, Simon (ARAMAZD: Armenian Journal of Near Eastern Studies, 2020)
In 1993 the Institute of Archaeology and Ethnography of the National Academy of Sciences and the Institute for Mycenaean, Aegean and Anatolian Studies (ISMEA) of the Italian National Council of Research (CNR) signed an agreement of co-operation that led to the joint archaeological survey in the Lake Sevan basin in the following years. The main aim of ISMEA, that had a long tradition of Urartian studies, was the study of that area as the north-eastern frontier of the Urartian kingdom, focusing in particular on the systems of territorial control.